EPF versus pension: The case of Malaysian public universities employees' decision - Tolos, Habibah; Abu Bakar, Arpah (2014)
This study seeks to examine the individual factors that influence the employees in making decision to enrol in either two types of mandatory retirement plans in Malaysian civil servants.A questionnaire survey comprised of 348 Malaysian public university employees has been conducted.Stratified random sample was adopted to collect primary data, which is then analyzed with logistic regression model.The results had identified the factors that have major effects on the choice of retirement schemes and reveal the patterns in which these factors influence employees’ choice. Knowledge and plan features are the most important variables to influence choice.Sources of retirement income, health status, mobility, extending work and decision-making processes have been found to be contributing factors in choice as well.Apart from academic purposes, this study will be beneficial to the government in improving the national retirement system, as well as to industry players in targeting potential customers for their retirement products.